Integrated decision-support system assessing investment trade-offs: IPSR Innovation Profile - Notenbaert, An Maria Omer; Hoek, Rein van der; Bahta, Sirak T.; Hammond, James; Burkart, Stefan; Baltenweck, Isabelle (CGIAR System Organization, 2022)
Failure to address constraints to livestock productivity and the growing risks from climate change and other shocks like the COVID-19 pandemic can limit productivity gains while putting sustainability at risk. Increasing yields through climate-smart interventions can contribute to lowering emissions intensities while enhancing livelihoods. But this is not always the case. It is therefore important to provide information about trade-offs between productivity, environmental impacts, and livelihood outcomes. Stakeholders need to understand what the trade-offs and synergies are between productivity, economics, gender & social equity, and environmental factors. So that they can be considered when developing and scaling livestock innovations and during policy making at national or regional level. In response to this challenge, we are developing a toolbox for scenario assessment that describes trade-offs and synergies associated with those scenarios at different scales. Such a decision-support system (integrating ex-ante modelling tools) helps researchers, development actors, donors, and governments to take trade-offs between social, economic, and environmental outcomes at different scales into account during evidence-based planning of investments in sustainable livestock production.